HOW DO SOCIO-DEMOGRAPHIC CHARACTERISTICS INFLUENCE THE PROBABILITY OF FINANCIAL INCLUSION? EVIDENCE FROM A TRANSITIONAL ECONOMY - Hong Thu Nguyen; Kieu Oanh Dao Le (Tạp chí Khoa học Đại học Đà Lạt)
Financial inclusion can be understood as the provision of financial services in a convenient and appropriate way to meet the needs of society, help vulnerable groups have opportunities, and promote sustainable economic growth. This study uses a probit regression model with 200 observations collected from November 1 to December 31, 2019, to examine how socio-demographic characteristics influence the probability of financial inclusion in Vietnam. The results show that human capital, education, and living in urban areas increase personal financial inclusion, while age has an inverse relationship with financial inclusion. Based on the analysis results, we recommend some solutions to promote financial inclusion, especially by applying financial technology and supplying more services to Vietnamese people.